Factor V Leiden Mutation and its Impact on Pregnancy Complications - Ľubica Hammerová; Ján Chabada; Juraj Drobný; Angelika Bátorová (Acta Medica, 2011)
Objective: The aim of this prospective study was to find the association between the factor V Leiden mutation and adverse pregnancy outcomes. Methods: This study is an analysis of a prospective observational study of the frequency of placenta-mediated complications of factor V Leiden mutation carriers. We compared pregnancy outcomes of 11 women with a heterozygous form of the factor V Leiden mutation with 41 women of a control group. Results: All pregnancies ended with delivery of a living infant. None of the 52 pregnancies were complicated by venous thromboembolism. There were a few significant differences regarding placenta-mediated complications. The gestational age at delivery showed small significant differences. There was a significant difference in the birth weight deviation in percentage between FVL carriers and controls. The incidence of blood loss exceeding 1000 ml was higher in the control group. Conclusions: Carriership of the factor V Leiden mutation did not affect the incidence of preeclampsia. Adverse pregnancy outcomes such as placental abruption were rare. Eclampsia, intrauterine fetal death and venous thromboembolism did not occur. Our results provide evidence that the maternal heterozygous FVL mutation did not increase the risk of an adverse pregnancy outcome.